Group cohesion and collaborative information behaviour: An exploration of student experiences of university group work - Khatamian Far, Parisa (2020)
Modern organisations heavily rely on using interdisciplinary teams to accomplish intellectually demanding tasks. The advent of the World Wide Web, the advancements in communication technological tools and easy access to high volumes of information through the Web provide expanded capacity for individuals to work together and fulfil their shared goal but true collaboration is far from straightforward. Teamwork skills are identified as a desirable and distinguishing attribute of the graduates whom employers seek to employ. Accordingly, higher education institutions lay particular emphasis on developing students’ collaborative skills by designing and incorporating group projects into courses. The findings of relevant research demonstrate that employers are still not satisfied with the newly-hired graduates’ performance and students also reflect negative attitudes towards university group work. In this regard, scholars attempt to gain a through and deep understanding of individuals’ collaborative information behaviour when working in group settings and identify the factors that can impact on this process. This research, guided by the primary question of ‘How does group cohesion shape students’ collaborative information behaviour over the duration of group tasks?’ sought to explore the development of cohesion in student groups which has been widely recognised as an influential element in motivating group members to work collectively. Through a series of supporting research questions addressing the role that task cohesion, social cohesion and perceived cohesion play in students’ collaborative information behaviour, the work also aimed to find out how different dimensions of cohesion can have an impact on the way students make sense of the group task components, search for information and use information to accomplish group projects. This study took a qualitative approach and used Straussian grounded theory methodology to collect and analyse the data. Data collection was conducted by taking an in-depth interview approach through 10 semi-structured focus group sessions with student participants recruited from an Australian university who were undertaking project units as part of their degrees across any number of discipline areas over two successive semesters. Data was analysed using open, axial and selective coding following the Strauss and Corbin approach. Constant comparison of similarities and differences in the data enabled the researcher to elaborate on the identified concepts in terms of their properties and dimensions. This study resulted in rich description of how different dimensions of group cohesion emerged and developed in student groups over the duration of completing the group task and its association with students’ collaborative and individual information behaviour practices. Results suggest that task cohesion exerted more meaningful impact on group process and outcomes in comparison with other aspects of cohesion. It was found that students’ collaborative information behaviour activities are shaped by their perceptions of group task cohesion developed through adopting shared leadership style, the level of task complexity and interdependence and group members’ composition in terms of similarity in aspirations and academic capability. With regard to social cohesion, familiarity was identified as a factor which had immediate impact on students’ feelings of attraction and liking towards the group which did not persist over time as it fell under the influence of group members’ commitment and active involvement in group task activities. Task cohesion was then recognised as an antecedent of social cohesion in student groups and participants’ interpretation of social cohesion was based on experiencing comfortable feeling with group members instead of developing collective sense of closeness and friendship. Experiencing such a feeling within the group plays a more influential role in motivating students to communicate easily and sharing their ideas In terms of perceived cohesion, the findings of this study indicated that students in this particular sample did not intend to develop a sense of belonging and attachment to the group. They were of the mindset that once they complete their group task, the group would be disbanded so there is no potential benefit of developing such a feeling in university group context. This study highlighted the role of task design and its features on students’ collaboration as well as their choice of communication method throughout the group’s lifespan. At the early stages of the group project, the level of collaboration for identification of needed information to create a shared focus and define the project’s problem statement was heavily dependent upon the nature of the assessment task and its perceived complexity. Individual information searching was also identified as a common characteristic among all the research participants in this study but the structure of the assessment task determined the level of collaboration among members in regard to sharing information and evaluating the retrieved information in terms of relevancy and credibility. The evaluation and use of information sources to fulfil group task requirements was seen to be a collaborative activity in similar research studies but the findings from this study showed that groups assigned a highly structured task did not feel a need to have regular communication because their sub-tasks were not so much related to each other. This finding suggests that the outcomes of collaboration are not what most academics expect them to be as too little emphasis placed on the role of the task and more on the scale of the work to be delivered. The key finding of this research is that the group ‘task’ drives the behaviours of students, as individuals and as a group member, and that assigning students a project to do as a group that is too large to be done individually will not drive genuine collaboration. This research suggests an addition to the Input, Mediator, Output, Input (IMOI) model that includes a Task Calibration step by academic staff, to define the primary outcome of any given assessment task as either ‘collaboration’ or ‘product’, rather than the hope that collaboration takes place in order to deliver a big product. This shows that true collaboration would not take place by assigning students a large-scale group project; instead the tasks should be designed and structured in a way to drive and reward collaboratio